Analisis sektor unggulan di Kabupaten Batanghari - Andi Syaputra; Hardiani Hardiani; Adi Bhakti (Konsentrasi Pembangunan Regional dan Publik, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2020)
This study aims to analyze the leading sectors in the economy in Batanghari Regency. This study uses secondary data for the period 2011-2017, sourced from the Central Statistics Agency of Jambi Province and Batanghari Regency. The analysis tools used are Location Quotient (LQ) analysis and Shift Share analysis. The results of the study found that the leading sectors in Batanghari Regency are the manufacturing industry sector, the government administration sector, defense, compulsory social security, and the education service sector. Keywords: Leading sector, Location quotient, Shift share